New lignans from anogeissus acuminata with HIV-1 reverse transcriptase inhibitory activity - Agnes M. Rimando (2018)
Anolignan A [1] and anolignan B [3] are new dibenzylbutadiene lignans isolated from Anogeissus acuminata. Compounds 1 and 3 were identified as the active HIV-1 reverse transcriptase (RT) inhibitory constituents of this plant obtained by bioassay-guided fractionation. Compound 3, which was very weakly active when tested alone, showed high activity when combined with 1. The activity of 1 was likewise enhanced in the presence of 3. A concave isobole obtained from a plot of data derived from assays with 1 and 3 in combination indicated their synergistic effects. Another new lignan, anolignan C [5], and a known lignan, (—)- secoisolariciresinol [10] , were also isolated from this plant. Compounds 5 and 10 did not have activity against HIV -1 RT. Compounds 1,3 and 5 were either weakly cytotoxic or noncytotoxic when tested in various cancer cell lines. The structures of 1–5 and 10 were established by spectroscopic methods, especially by 1D and 2D nmr experiments. © 1994, American Chemical Society. All rights reserved.